2019
DOI: 10.1088/1757-899x/560/1/012121
|View full text |Cite
|
Sign up to set email alerts
|

Operating modes of vacuum plasmatrons with hollow cathodes

Abstract: Results of experimental studies of starting characteristics of vacuum plasma torches in glow discharge mode with switching to abnormal glow discharge and arc discharge are presented. It is demonstrated that if high-frequency current source is used parallel to direct current, ion current is increased and the time of starting mode is reduced. Experimental smelts of tantalum, tungsten, molybdenum, zirconium, and titan were carried out in operating modes with measurement of liquid metal surface temperature in rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…209 A first plasma torch is used in the gasifier, while an electric-arc plasma torch in the second reactor maintains the temperature at 1300-1500 1C. 209,210 Vishwajeet et al conducted experiments using a two-stage gasification system coupling a prototype-entrained flow plasma-assisted gasification reactor with ex-situ plasma vitrification. 211 They showed that although the use of plasma positively affects the quality of the raw syngas, the dilution by plasma gases such as N 2 leads to a low calorific value of the dry syngas.…”
Section: Energy and Environmental Science Reviewmentioning
confidence: 99%
“…209 A first plasma torch is used in the gasifier, while an electric-arc plasma torch in the second reactor maintains the temperature at 1300-1500 1C. 209,210 Vishwajeet et al conducted experiments using a two-stage gasification system coupling a prototype-entrained flow plasma-assisted gasification reactor with ex-situ plasma vitrification. 211 They showed that although the use of plasma positively affects the quality of the raw syngas, the dilution by plasma gases such as N 2 leads to a low calorific value of the dry syngas.…”
Section: Energy and Environmental Science Reviewmentioning
confidence: 99%
“…Erosion of the multi-arc cathode (Fig. 6) was determined by the mass loss [4]. Each launch lasted from 30 to 50 minutes.…”
Section: Air-plasma Cutting Of Metalsmentioning
confidence: 99%